Validazione di uno strumento per valutare la partecipazione alle attività extracurriculari in area STEM. Il questionario Science Activities Evaluation Engagement (SAEE) - Italo Testa; Giovanni Costanzo; Alessio Parlati; Francesca Tricò (LED Edizioni Universitarie, 2021)
In this study, we present a new questionnaire, the Science Activities Evaluation Engagement (SAEE) instrument, for the evaluation of the students' engagement in STEM oriented extra-curricular activities. The questionnaire was administered to about 1000 secondary school students who participated in the activities of the Piano Nazionale Lauree Scientifiche in Biology, Chemistry and Physics. Through an exploratory and confirmatory factor analysis, it was possible to validate a four-factor structure of the instrument: Satisfaction with the followed activities; Utility of the activities; Difficulties in following the activities; Involvement of close people. The obtained factor structure shows a good model fit, with each of the obtained scales showing an excellent reliability. Criterion validity was established through the academic motivation scale. The proposed instrument shows also an adequate convergent validity and a sufficient discriminant validity. Implications of the study for the evaluation of Third Mission activities of the Italian universities are also briefly discussed.